2012
DOI: 10.1111/j.1399-5618.2012.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Trait and state corticostriatal dysfunction in bipolar disorder during emotional face processing

Abstract: Objectives Convergent evidence supports limbic, anterior paralimbic, and prefrontal cortex (PFC) abnormalities in emotional processing in bipolar disorder (BD) and suggests that some abnormalities are mood-state-dependent and others persist into euthymia. However, few studies have assessed elevated, depressed, and euthymic mood states while individuals processed emotional stimuli of varying valence to investigate trait- and state-related neural system responses. Here, regional brain responses to positive, nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 83 publications
3
49
0
Order By: Relevance
“…Consistent with right-lateralized abnormalities, studies have reported reduced right frontal GM volume (72,73) and right UF WM integrity (53,60). PFC functional abnormalities in mania in BD have also tended to be right-sided (7477). These findings suggest that the right hemisphere abnormalities observed in this study might be related to increased risk for mania.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with right-lateralized abnormalities, studies have reported reduced right frontal GM volume (72,73) and right UF WM integrity (53,60). PFC functional abnormalities in mania in BD have also tended to be right-sided (7477). These findings suggest that the right hemisphere abnormalities observed in this study might be related to increased risk for mania.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, other studies found that euthymic BD-I patients did not differ from normal controls while processing negative faces or passively viewing negative images, whereas differences were observed while processing happy/neutral faces (Liu et al, 2012) or during a down-regulation task (Townsend et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Emotional dysregulation in BD has also been linked to atypical functional hemispheric asymmetries as shown by neuroimaging studies (Yurgelun-Todd et al, 2000;Foland et al, 2008;Killgore et al, 2008;Strakowski et al, 2011;Liu et al, 2012) suggesting a deviation from the typical right hemisphere advantage in emotion perception. For example, Killgore et al, (2008) found a decrease in right inferior orbitofrontal activation in BD patients with manic symptoms during passive viewing of a series of black and white fearful facial expressions.…”
Section: Introductionmentioning
confidence: 96%